1980
DOI: 10.1051/rnd:19800726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentable carbohydrates on volatile fatty acids, ammonia and mineral absorption in the rat caecum

Abstract: Summary. The Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…One possibility is that this may function as a mechanism to facilitate absorption after a meal. Although most absorption occurs in the small intestine, a significant quantity of nutrients (including lactose, lactulose, and starches) are fermented into SCFA in the large intestine (in animals, 27,[49][50][51][52][53][54][55][56][57] as well as in humans [58][59][60][61][62][63][64][65][66] ). We hypothesize that SCFA concentrations would peak in vessels serving the gut after a meal, and that this increase in SCFAs results in local vasodilation (as shown previously in ref.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that this may function as a mechanism to facilitate absorption after a meal. Although most absorption occurs in the small intestine, a significant quantity of nutrients (including lactose, lactulose, and starches) are fermented into SCFA in the large intestine (in animals, 27,[49][50][51][52][53][54][55][56][57] as well as in humans [58][59][60][61][62][63][64][65][66] ). We hypothesize that SCFA concentrations would peak in vessels serving the gut after a meal, and that this increase in SCFAs results in local vasodilation (as shown previously in ref.…”
Section: Discussionmentioning
confidence: 99%
“…In cecectomized rats, the digestibility of crude ash and ratio of ash accumulation to the amount consumed were increased after consumption of a 5% mannitol-or 5% FOS-containing diet. Stimulatory effects of indigestible sugars, such as FOS, on mineral absorption and utilization in the body have been reported (29)(30)(31)(32), although the stimulated absorption of minerals did not always result in increased retention of minerals (30). The effects of fermentable sugars on the absorption of minerals differ depending on the type of mineral and region of the intestine.…”
Section: Concentration and Accumulation Of Body Componentsmentioning
confidence: 99%
“…Stimulation of calcium and magnesium absorption by FOS occurs in both the small and large intestine (32). It is thought that the stimulatory effects of indigestible sugars on mineral absorption occur via a transepithelial diffusion route in the small intestine (33) and solubilization of minerals (29) and/or activation of absorptive cells (34) by SCFAs produced from fermentable sugars in the large intestine. It is therefore suggested that the stimulatory effects of mannitol on the absorption and retention of minerals in both normal and cecectomized rats in this experiment were caused by the actions of mannitol in the small intestine, independently of the production of organic acids in the cecum.…”
Section: Concentration and Accumulation Of Body Componentsmentioning
confidence: 99%
“…Along the length of the intestine, the duodenum and proximal jejunum are generally considered to be the most active segments for the absorption of nutrients, but other evidence indicates that the cecum and the colon of the large intestine are also responsible for calcium and magnesium absorption (43). Many reports have described a significant correlation between increases in mineral absorption and the fermentation of indigestible carbohydrates in the large intestine (9,10,(23)(24)(25).…”
Section: Increased Calcium Absorption With Fos Occurs In the Large Inmentioning
confidence: 99%